Blood pressure and the capacity‐load model in 8‐year‐old children from Nepal: Testing the contributions of kidney size and intergenerational effects. Issue 4 (5th February 2016) - Wells, Jonathan C.K.; Devakumar, Delan; Grijalva‐Eternod, Carlos S.; Manandhar, Dharma S.; Costello, Anthony; Osrin, David
Abstract : Objectives: Growth patterns in early life are increasingly linked with subsequent cardio‐metabolic risk, but the underlying mechanisms require elucidation. We have developed a theoretical model of blood pressure, treating it as a function of homeostatic metabolic capacity, and antagonistic metabolic load. We sought to differentiate prenatal and postnatal components of metabolic capacity, and to identify intergenerational contributions to offspring capacity and load. Methods: We followed up at 8 years a cohort of children originally recruited into a randomized trial of maternal micronutrient supplementation in pregnancy. Maternal anthropometry was measured at recruitment. Offspring anthropometry was measured at birth, 2 years and 8 years. Offspring blood pressure, kidney size, and body composition were measured at 8 years. Regression analysis was used to investigate potential associations of maternal phenotype, birth phenotype, and current body composition with kidney size and blood pressure. Results: Blood pressure was positively associated with body fat, but negatively associated with birth weight and relative leg length. Kidney size was positively associated with birth weight but not with relative leg length. Adjusting for adiposity, blood pressure was independently negatively associated with birth weight, relative leg length, and kidney length. Maternal height and BMI predicted offspring size at birth and at 8 years, but not blood pressure. Conclusions: Our data provide support for the capacity‐load model of blood pressure in Nepalese children. Fetal and postnatal growth and kidney dimensions all contribute to metabolic capacity. Maternal phenotype contributed to offspring capacity and load, but these associations did not propagate to blood pressure. Am. J. Hum. Biol. 28:555–565, 2016. © 2016 The Authors American Journal of Human Biology Published by Wiley Periodicals, Inc